TINJAUAN TEORITIS MANAJEMEN MUTU PENDIDIKAN - Na'im, Zaedun (STAI Ma'had Aly Al-Hikam Malang, 2024)
When discussing the results of educational provision, of course you will question the quality of educational provision, and to measure the quality of education you can look at the graduates or output. And this can be realized if it is done with proper management of the quality of education, and that is the domain of education quality management studies. So a comprehensive understanding of education quality management is needed so that it can be implemented in educational institutions appropriately and can run effectively and efficiently. In this study the author uses qualitative research with a library research approach and is descriptive in nature, where the author wants to reveal a deeper theoretical review of education quality management.